Amendoim inoculado com estirpes de rizóbio em latossolo do Cerrado mato-grossense - Almeida, Milly Siqueira Cardinal de (2017)
Peanut (Arachis hypogaea L.), is widely used in human consumption, consumed worldwide, has high nutritional value and energy can around 40 to 50% of unsaturated oils. Because it is a legume, it obtains greater part of nitrogen the atmosphere, through the Biological Fixation of Nitrogen, which is the association, these plants with bacteria known as rhizobia. The technique of inoculating peanut seeds with bacteria has been responsible for significant cost savings, as well as greater sustainability in agricultural production, to reduce the use of nitrogenous fertilizers. Was evaluated the effectiveness of inoculation of rhizobia strains on the development of peanut plants and their effect on nodulation along three soil layers (0-10 cm, 10-20 cm and 20-30 cm) were evaluated in this work. The conduction of this essay occurred in a greenhouse at the Federal University of Mato Grosso, University Campus of the Rondonópolis-MT. The experimental design was completely randomized with six treatments and six replicates, consisting of three strains of rhizobia (MT08 and MT15 - Rhizobium tropici, and MT16 - R. leguminosarum), one commercial inoculant (SEMIA 6144) and two controls. An absolute witness (without fertilization) and another with nitrogen fertilization (50 mg dm-3 of urea). The variables height of the plants, Falker chlorophyll index at 30 and 50 days after emergence (DAE), number of nodules, dry mass of nodules, dry mass of grains, sheet dry mass, dry mass of roots, dry mass Total, N-total sheet and grains, crude protein of the grains. The results were submitted to analysis of variance and the treatments were compared using orthogonal contrast using the statistical program SISVAR. Peanut significantly responded to treatments with inoculant from the rhizobia strains, the best being obtained with the MT15 strain in the variables Falker chlorophyll index (at 30 days after emergence), number of nodules, shoot dry mass, dry mass of Roots, total dry mass, nitrogen accumulation in the grains and relative efficiency. In the variables dry mass of nodules and weight of 100 seeds, the strain that presented better performance was the MT16. For the Falker chlorophyll index (50 days after emergence), nitrogen accumulation in the aerial part, nitrogen concentration in the grains and crude protein content of the grains, the plants fertilized with mineral nitrogen presented superior performance to the other treatments. The number of nodules, dry mass of nodules and dry mass of roots analyzed separately per layer showed higher values in the 0-10 cm layer. It was concluded that the strains showed potential for use as an inoculant for peanuts, especially MT15, and that most of the nodulation occurs in the first two layers of 0-10cm and 10-20cm in depth.